EVALUASI KELAYAKAN FINANSIAL USAHA PETERNAKAN KAMBING (Studi Kasus: Azka Amanah Farm) - Afrialdi; Rina Febrinova; Defi Delwina (Universitas Pasir Pengaraian, 2025)
This study analyzes the financial feasibility of the dairy goat farming business at Azka Amanah Farm, located in Rambah Village, Rambah Hilir District. The research aims to examine the business profile, analyze income, and assess the financial feasibility of the enterprise. A case study approach was used, applying quantitative analysis to evaluate cash flow and financial feasibility. The results indicate that the business is managed systematically, with the selection of superior livestock breeds, a planned breeding pattern, and high-quality feed provision. The farm's revenue has significantly increased yearly, mainly from the sale of goat kids, feces, urine, and milk. Financial analysis shows that the business is profitable, with an NPV of Rp. 377.922.948, an IRR of 66%, a Net B/C ratio of 3.11 (>1), and a Payback Period of 1 year, 4 months, and 11 days. These findings indicate that the dairy goat farming business at Azka Amanah Farm is financially feasible and has promising prospects for further development.